IMPROVING THE STUDENTS’ VOCABULARY MASTERY BY USING WORD SQUARE MEDIA COMPARATIVE STUDY OF USING KWL AND QAR STRATEGIES ON STUDENTS’ READING COMPREHENSION - Sri - Lestari (Intensive Journal, 2023)
Reading is a complex activity. Through reading activities, readers have responses like rejection, acceptance, and criticism of what they have read. Therefore, appropriate strategies are needed in reading learning activities for students to facilitate reading comprehension. This study aims to determine significant differences in using KWL and QAR strategies on students' reading comprehension abilities.This study used an experimental method with a post-test-only design. The population in this study were students of class VIII SMPN 5 Banjarmasin. The sampling technique used in this study was using a saturated sampling technique for as many as 261 students. The instrument used was multiple choice questions in the form of a post-test. The data analysis technique in this study was the t-test at a significance level of 5%.The results showed that the student's reading comprehension who were taught by using the KWL strategy was 52.09 lower than those of the students taught by using the QAR strategy of 57.09 with a tcount of 2.251 and a p of 0.025 (p < 0.05 ). The difference in the post-test mean of reading comprehension skills in the KWL strategy group and the QAR strategy group was 5.00. This shows that there is a significant difference in the use of KWL and QAR strategies on the reading comprehension skills of eight grade students at SMPN 5 Banjarmasin.